Seeking a Future for the Past Space, Power, and Heritage in a Chinese City (University of Michigan Press, 2024)
Seeking a Future for the Past: Space, Power, and Heritage in a Chinese City examines the complexities and changing sociopolitical dynamics of urban renewal in contemporary China. Drawing on ten years of ethnographic fieldwork in the northeastern Chinese city of Qingdao, the book tells the story of the slow, fragmented, and contentious transformation of Dabaodao-an area in the city's former colonial center-from a place of common homes occupied by the urban poor into a showcase of architectural heritage and site for tourism and consumption. The ethnography provides a nuanced account of the diverse experiences and views of a range of groups involved in shaping, and being shaped, by the urban renewal process-local residents, migrant workers, preservationists, planners, and government officials-foregrounding the voices and experiences of marginal groups, such as migrants in the city. Unpacking structural reasons for urban developmental impasses, it paints a nuanced local picture of urban governance and political practice in contemporary urban China. Seeking a Future for the Past also weighs the positives and negatives of heritage preservation and scrutinizes the meanings and effects of "preservation" on diverse social actors. By zeroing in on the seemingly contradictory yet coexisting processes of urban stagnation and urban destruction, the book reveals the multifaceted challenges that China faces in reforming its urbanization practices and, ultimately, in managing its urban future.
English
Keywords: Social & cultural anthropology, ethnography; Society & culture: general; Urban communities